The Effect of Product Differentiation and Brand Image on repurchase interest Scarlett Whitening Products (Case Study of Scarlett Body Lotion Products in the People of Pulau Rakyat Asahan Distric) - Dahrul Siregar (JEBIM Prima, 2023)
The purpose of this study was to determine